EVALUATING WRITING LEARNING ASSESSMENT IN HIGH SCHOOL USING CONTEXT, INPUT, PROCESS, AND PRODUCT (CIPP) MODEL - Nugraha, Haris Santosa; Syihabuddin, Syihabuddin; Mulyati, Yeti; Damayanti, Vismaia S. (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2024)
Effective and efficient assessment of writing learning plays an important role in improving students' writing ability. Students' writing skills tend to be low so that they have not been able to achieve the expected learning objectives. Therefore, this study aims to evaluate the implementation of high school students' writing learning assessment using the Context, Input, Process, and Product (CIPP) model. This evaluative method was conducted at high schools in the Bandung Raya area using purposive sampling technique. The research sample consisted of 120 students, 6 teachers, and 3 school leaders. Data were collected through questionnaires, interviews, and documentation which were analyzed using descriptive data analysis. The findings showed that the evaluation of the implementation of the assessment of learning to write on the average components of context, input, process, and product was in the good enough category with an average score of 2.91 and 2.87. The evaluation aspects analyzed include conditions, needs, teacher competencies, learner characteristics, availability of facilities and infrastructure, planning, implementation, implementation results, and the impact of the implementation of writing learning assessment in high school. Based on the findings of the analysis, improvement efforts are needed, especially in the component of writing learning assessment products that can be adapted to the diversity of students.